2011
DOI: 10.1590/s1983-14472011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Câncer de colo uterino: atenção integral à mulher nos serviços de saúde

Abstract: integral à mulher nos serviços de saúde. Rev Gaúcha Enferm., Porto Alegre (RS) 2011 set;32(3):502-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
15

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 10 publications
(2 reference statements)
0
7
0
15
Order By: Relevance
“…Thus, it is essential scientific knowledge of professionals, user opening it to new behaviors, to create bonds, determining factors and facilitating the development of health comprehensiveness. 15,17 To consider the subject as a conscious and free to make choices, we observed that this subject does not exist in Maffesoli. There is the individual in rational times or the person in emotional times.…”
Section: Then It's Up To the Manager To The Statistics Of Immunizatiomentioning
confidence: 99%
“…Thus, it is essential scientific knowledge of professionals, user opening it to new behaviors, to create bonds, determining factors and facilitating the development of health comprehensiveness. 15,17 To consider the subject as a conscious and free to make choices, we observed that this subject does not exist in Maffesoli. There is the individual in rational times or the person in emotional times.…”
Section: Then It's Up To the Manager To The Statistics Of Immunizatiomentioning
confidence: 99%
“…A qualitative study on cervical cancer conducted in southern Brazil showed that the provision of comprehensive care for women implies the acknowledgment of an action-based logic that considers their individual and collective needs within their social context (13) , which could be favoured at the studied family health care units. In this sense, actions that seek to expand coverage and follow-up should be implemented.…”
Section: Summary Indicators N %mentioning
confidence: 99%
“…Ganha relevância o conhecimento relativo à magnitude desse problema, mas também às características socioeconômicas e culturais das mulheres que são acometidas por essa doença, à identificação dos riscos e à demanda de estratégias com planejamento para prevenção e controle, através de ações assistenciais e/ou educativas [1][2][3][4][5] . DOI: http://dx.doi.org/10.12957/reuerj.…”
Section: Introductionunclassified